2010
DOI: 10.1053/j.seminoncol.2010.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Principles of Cancer Screening: Lessons From History and Study Design Issues

Abstract: Early detection of cancer has held great promise and intuitive appeal in the medical community for well over a century. Its history developed in tandem with that of the periodic health examination, in which any deviations-subtle or glaring--from a clearly demarcated "normal" were to be rooted out, given the underlying hypothesis that diseases develop along progressive linear paths of increasing abnormalities. This model of disease development drove the logical deduction that early detection-by "breaking the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
161
2
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(179 citation statements)
references
References 63 publications
3
161
2
9
Order By: Relevance
“…Over-diagnosis is often defined as the detection of tumours that, if left untreated, would not lead to symptoms or harm to the individual within the individual's lifetime [13,14]. Over-diagnosis can occur if there are tumours that lack true malignant potential or if they are so slow-growing that the individual would die due to other causes before her life is threatened by the cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over-diagnosis is often defined as the detection of tumours that, if left untreated, would not lead to symptoms or harm to the individual within the individual's lifetime [13,14]. Over-diagnosis can occur if there are tumours that lack true malignant potential or if they are so slow-growing that the individual would die due to other causes before her life is threatened by the cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Lead-time is survival time that is added to a patient's survival time because of an earlier diagnosis irrespective of a possibly postponed time of death [13,14]. In the presence of lead-time, the survival times of the patients are prolonged by an early diagnosis, and the survival proportion at any given time point is therefore increased even if no real improvement in survival is experienced.…”
Section: Introductionmentioning
confidence: 99%
“…Egyrészt pszichológiailag kedvezőtlen hatással van a betegre, szorongást és depressziót válthat ki, másrészt a pozitív eredmény után a beteg további kivizsgáláson, beavatkozásokon eshet át, amelyek mellékhatásokat okozhatnak, valamint jelentős anyagi terhet jelenthetnek a betegnek és az egészségügyi rendszernek egyaránt [41]. A modellépítés során a szűréshez kapcsolódó negatív hatásokat, a költségekhez hasonlóan, figyelembe kell venni.…”
Section: A Modellépítéshez Szükséges Adatokunclassified
“…A tapasztalatok azt mutatják, hogy azok, akik a részvétel mellett döntenek, magasabb iskolai végzettsé-gűek, jobb anyagi helyzetűek és fogékonyabbak az egészséget érintő témákra, így több testmozgást végez-nek, kevesebbet dohányoznak és kevesebb alkoholt fogyasztanak [41]. Ezáltal a szűrésen részt vevőknek általá-nosságban jobb az egészségi állapotuk és jobbak az életkilátásaik, mint a szűrést elutasítóknak, amely az ön-kéntes részvételből származó torzításhoz vezet.…”
Section: Megbeszélés éS Limitációkunclassified
“…44 Finally, although some screening studies have suggested improvements in lung cancer mortality in the screened population, other investigators have suggested that this may simply be due to detection of cancer earlier within its natural history or so-called 'lead-time' bias. 45 …”
Section: Chest X-ray and Computed Tomography Screeningmentioning
confidence: 99%